2022
DOI: 10.1038/s41467-022-28130-0
|View full text |Cite
|
Sign up to set email alerts
|

Low CCR5 expression protects HIV-specific CD4+ T cells of elite controllers from viral entry

Abstract: HIV elite controllers maintain a population of CD4 + T cells endowed with high avidity for Gag antigens and potent effector functions. How these HIV-specific cells avoid infection and depletion upon encounter with the virus remains incompletely understood. Ex vivo characterization of single Gag-specific CD4 + T cells reveals an advanced Th1 differentiation pattern in controllers, except for the CCR5 marker, which is downregulated compared to specific cells of treated patients. Accordingly, controller specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 69 publications
(82 reference statements)
5
30
0
Order By: Relevance
“…Several studies have shown that PBMCs from ECs have a miRNA repertoire that is distinct from that of HIV-1 ART-naïve progressors, and such a difference may in part explain the control of viral infection in ECs ( Witwer et al., 2012 ; Reynoso et al., 2014 ; Ayala-Suárez et al., 2020 ). In this context, we assessed the levels of miRNA-103 and CCR5 mRNA in CD4 + T cells from ECs and ART-naïve progressors and found that CCR5 mRNA in CD4 + T cells obtained from ECs was significantly decreased when compared to that in CD4 + T cells from ART-naïve progressors, in line with recently published results ( Claireaux et al., 2022 ; Gonzalo-Gil et al., 2019 ; Meijerink et al., 2014 ). Thus, in addition to displaying specific immune signatures ( Krishnan et al., 2014 ; Nguyen et al., 2019 ), ECs could also control HIV-1 infection by limiting CCR5 expression levels, particularly in HIV-1-specific CD4 + T cells, via multiple mechanisms, a characteristic that results in decreased susceptibility to viral infection and depletion ( Claireaux et al., 2022 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several studies have shown that PBMCs from ECs have a miRNA repertoire that is distinct from that of HIV-1 ART-naïve progressors, and such a difference may in part explain the control of viral infection in ECs ( Witwer et al., 2012 ; Reynoso et al., 2014 ; Ayala-Suárez et al., 2020 ). In this context, we assessed the levels of miRNA-103 and CCR5 mRNA in CD4 + T cells from ECs and ART-naïve progressors and found that CCR5 mRNA in CD4 + T cells obtained from ECs was significantly decreased when compared to that in CD4 + T cells from ART-naïve progressors, in line with recently published results ( Claireaux et al., 2022 ; Gonzalo-Gil et al., 2019 ; Meijerink et al., 2014 ). Thus, in addition to displaying specific immune signatures ( Krishnan et al., 2014 ; Nguyen et al., 2019 ), ECs could also control HIV-1 infection by limiting CCR5 expression levels, particularly in HIV-1-specific CD4 + T cells, via multiple mechanisms, a characteristic that results in decreased susceptibility to viral infection and depletion ( Claireaux et al., 2022 ).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, so far, cases of sterilizing cure have been achieved in patients that received allogeneic hematopoietic stem cell transplantation (HSCT) from donors homozygous for the CCR5-Δ32 deletion, which impairs surface expression of the CCR5 receptor and therefore confers resistance to infection ( Gupta et al., 2019 , 2020 ; Hütter et al., 2009 ). Furthermore, highly functional HIV-1-specific CD4 + T cells of ECs were found less susceptible to HIV-1 entry owing to a negative regulation of the CCR5 co-receptor, a characteristic that appears to protect these cells from depletion and promote HIV-1 control ( Claireaux et al., 2022 ; Gonzalo-Gil et al., 2019 ; Meijerink et al., 2014 ). Thus, understanding how CCR5 is regulated in CD4 + T cells is essential for the development of CCR5-targeted therapies aimed at reducing the establishment of latent viral reservoirs and achieving a functional HIV-1 cure.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous controllers do not experience sustained levels of viremia and have protective genetic backgrounds such as CCR5Δ32 or protective HLA alleles that are different from most people living with HIV. 44 , 45 , 46 , 47 Therefore, HIV-specific CD8 + T cells in spontaneous controllers might not be the best comparator to determine the level of functionality of HIV-specific CD8 + T cells in people on ART. Comparing the functionality of HIV-specific CD8 + T cells in people who initiated ART during AHI or CHI allows to compare individual with similar genetic backgrounds but having experienced different HIV antigen burden prior to ART.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that the host factors and effective immunologic response plays crucial role in controlling the infection ( 91 , 92 ) . A recent study has shown that HIV-specific CD4+ T cells of controllers express low levels of CCR5, which inhibits the entry of HIV-1 ( 93 ) . Thus, the CCR5 represents a target with multifaceted effects in the case of HIV-1 pathogenesis and disease progression.…”
Section: Discussionmentioning
confidence: 99%